In silico analysis of the HSP90 chaperone system from the African trypanosome, Trypanosoma brucei - Jamabo, Miebaka; Bentley, Stephen John; Macucule-Tinga, Paula; Tembo, Praise; Edkins, Adrienne Lesley; Boshoff, Aileen (Frontiers in Molecular Biosciences, 2022)
African Trypanosomiasis is a neglected tropical disease caused by Trypanosoma brucei (T. brucei) and spread by the tsetse fly in sub-Saharan Africa. The trypanosome relies on heat shock proteins for survival in the insect vector and mammalian host. Heat shock protein 90 (HSP90) plays a crucial role in the stress response at the cellular level. Inhibition of its interactions with chaperones and co-chaperones is being explored as a potential therapeutic target for numerous diseases. This study provides an in silico overview of HSP90 and its co-chaperones in both T. brucei brucei and T. brucei gambiense in relation to human and other trypanosomal species, including non-parasitic Bodo saltans and the insect infecting Crithidia fasciculata. A structural analysis of T. brucei HSP90 revealed differences in the orientation of the linker and C-terminal domain in comparison to human HSP90. Phylogenetic analysis displayed the T. brucei HSP90 proteins clustering into three distinct groups based on subcellular localisations, namely cytosol, mitochondria and endoplasmic reticulum. Syntenic analysis of cytosolic HSP90 genes revealed that T. b. brucei encoded for 10 tandem copies, while T. b. gambiense encoded for 3 tandem copies; L. major had the highest gene copy number with 17 tandem copies. The updated information on HSP90 from recently published proteomics on T. brucei was examined for the different life cycle stages and subcellular localizations. The results show a difference between T. b. brucei and T. b. gambiense with T. b. brucei encoding a total of twelve putative HSP90 genes, while T. gambiense encodes five HSP90 genes. Eighteen putative co-chaperones were identified with one notable absence being cell division cycle 37 (Cdc37). These results provide an updated framework on approaching HSP90 and its interactions as drug targets in the African trypanosome.